An implementation of ergonomics in working environment at NXP Semiconductors Malaysia / Norbaizura Shamaruddin - Shamaruddin, Norbaizura (Faculty of Business and Management, 2011)
This study is focus on an implementation of ergonomics working environment. The first objective of this research is to study about the level of awareness of ergonomics in working environment at NXP Semiconductors Malaysia. Secondly the objective is to determine the most dominant factors that contribute to the implementation of ergonomics working environment. Thirdly the objective is to study the implication of implementation of ergonomics working environment at NXP Semiconductors Malaysia. All the objectives were using some method in analyze the result. For the first and third objective, the researcher used descriptive analysis in order to get the result. Descriptive analysis wants to measure the ranges of mean from the result. Pearson’s correlation coefficient also used by the researcher to determine the direction and significant level of relationship between dependent and independent variable. Then, the researcher knows the most dominant factor that contributes to the implementation. It shows that the job requirement is the variable that most contribute to the implementation of ergonomics working environment at NXP Semiconductors Malaysia. From the research, the researcher can conclude that all the independent variables are significant in this study. The researcher also provides some recommendation to solve some problem arise. The researcher would suggest that the organization should provide awareness programme to educate the staffs. In addition, the researcher also recommend that workers need to participate in all programme provide by the organization. The researcher suggests that the organization should provide the equipment’s that user-friendly to the workers. The organization should provide ergonomics training to the workers in order to avoid them from suffering any injuries. Furthermore, the researcher also suggests that the communication also important as a medium in implementing ergonomics working environment.